¿Te vas o te quedas? variations in explations for housing abandonment in Tijuana, México - Lara García, Francisco (Premio Internacional de Tesis de Investigación sobre Vivienda y Desarrollo Sustentable 2016. La Vivienda Social Innovación y Tecnología, 2016)
Tijuana, a city along the Mexican border with the United States, is currently suffering from a housing abandonment crisis. Various explanations have been offered to explain the occurrence of the phenomenon, but none of these satisfactorily account for the uneven distribution of abandonment in the city. This study explores the variations in explanations for housing abandonment through a mixed-methods investigation. It finds that the "distance" that stakeholders have from the problem of abandonment has an effect on the complexity of explanations that these actors are likely to offer. It concludes with a discussion of the implications of this finding on Mexican housing policy, ending with prospective policy paths that could incorporate more effectivemulti-scalar, multi-agent approaches to housing provision.